Comparison of Bispectral Index-Guided Administration of Desflurane and Propofol for Endoscopic Transnasal Transsphenoidal Resection of Pituitary Tumors - Bharadwaj, Devika; Mahajan, Charu; Aggarwal, Richa; Prabhakar, Hemanshu; Chaturvedi, Arvind (Journal of Neuroanaesthesiology and Critical Care, 2020)
Background Use of short-acting anesthetic agents such as propofol and desflurane allows rapid awakening and prompt neurological assessment of patients undergoing endoscopic transnasal transsphenoidal resection of pituitary tumors. However, there are no studies comparing the effect of these two agents in these patients. We performed this study to compare the intraoperative hemodynamics and postoperative recovery characteristics of patients undergoing endoscopic transnasal transsphenoidal (TNTS) pituitary tumor surgery using bispectral index (BIS)-guided administration of desflurane and propofol.Materials and Methods In this prospective, randomized trial, 60 patients undergoing endoscopic TNTS pituitary surgery were randomized to receive BIS-guided administration of either propofol (Group P) or desflurane (Group D) for the maintenance of anesthesia. Heart rate (HR), mean arterial pressure (MAP), intraoperative complications, time to emergence, extubation, cognition, and modified Aldrete score were evaluated. Statistical analysis was performed using STATA 12.0. Categorical and continuous variables were compared between the groups using Fisher’s exact test and t-test, respectively. Emergence from anesthesia and hemodynamics at various stages of surgery was compared between the groups using Wilcoxon rank sum test. The p-value < 0.05 was considered statistically significant.Results The HR was significantly higher at all stages of surgery in group P (p = 0.01). MAP was comparable between the groups at various time points (p > 0.05). Both emergence time (8.5 vs. 15 minutes; p < 0.00) and extubation time (10 vs. 17.5 minutes; p < 0.00) were significantly shorter in Group D compared with Group P. Modified Aldrete score at 5 and 10 minutes after extubation was higher with desflurane than propofol, but early cognition was comparable between the two groups.Conclusion The hemodynamics and early cognition score were comparable in patients receiving propofol or desflurane. Desflurane provides rapid emergence and recovery when compared with propofol.
Keywords: endoscopic transnasal transsphenoidal pituitary tumor surgery; bispectral index; postoperative cognition; propofol; desflurane